2010
DOI: 10.1186/1423-0127-17-s1-s7
|View full text |Cite
|
Sign up to set email alerts
|

Protection effect of taurine on nitrosative stress in the mice brain with chronic exposure to arsenic

Abstract: BackgroundArsenic exposure induces overproduction of reactive nitrogen species (RNS) in brain tissue and results in nucleic acid damage to the nerve cells. The 8-nitroguanine is one of the major products formed by the reaction of guanine, and ONOO-, and has been used as a popular biomarker of nucleic acid damage due to RNS attacking. In the present study, we examined whether the administration of taurine can protect against nucleic acid damage of brain neurons by arsenic-induced RNS.Materials and methodsSixty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 73 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, compared with temozolomide, bevacizumab and other expensive drugs, As 2 O 3 is an affordable drug with minimal economic concerns and can benefit the maximum number of GBM patients. A study in mice has demonstrated that As 2 O 3 is able to enter brain [ 44 ]. Although the infusion and efficiency of As 2 O 3 in human brain tumors remained to be further determined, it's likely that As 2 O 3 as a small molecular drug can pass through the blood brain barrier to inhibit GBM tumor growth by targeting GSCs in human brains.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared with temozolomide, bevacizumab and other expensive drugs, As 2 O 3 is an affordable drug with minimal economic concerns and can benefit the maximum number of GBM patients. A study in mice has demonstrated that As 2 O 3 is able to enter brain [ 44 ]. Although the infusion and efficiency of As 2 O 3 in human brain tumors remained to be further determined, it's likely that As 2 O 3 as a small molecular drug can pass through the blood brain barrier to inhibit GBM tumor growth by targeting GSCs in human brains.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 8-nitroguanine is a potentially mutagenic DNA lesion, which can participate in initiation and promotion in the infection-related carcinogenesis (Loeb & Preston, 1986;. Our studies have demonstrated that 8-nitroguanine is formed at the sites of carcinogenesis in humans and experimental animals (Ma et al, 2004;Pinlaor et al, 2004b;Ding et al, 2005;Horiike et al, 2005;Ma et al, 2006;Hoki et al, 2007a;Hoki et al, 2007b;Fujita et al, 2008;Ma et al, 2008;Tanaka et al, 2008;Ma et al, 2009;Ma et al, 2010). Moreover, our studies have demonstrated that 8-nitroguanine was formed in Oct3/4-positve stem cells in S. haematobium-associated cystitis and cancer tissues.…”
Section: Introductionmentioning
confidence: 75%
“…Such antidote effects of taurine or high capacity for taurine uptake into the cells (or conversely harmful effects of taurine depletion) have i.a . been found against alcohol (2340), against the analgesic and fever-depressing drug acetaminophen (also called paracetamol) (4144), against the aminoglycoside antibacterial drug gentamicin (4547), against the immunosuppressant drug cyclosporine A (48, 49), against the anticancer drugs cisplatin (5054), doxorubicin (also called adriamycin) (5562), bleomycin (6378), methotrexate (79) and taumustine (80), against the cytokine interleukin-2 (IL-2), which is used for immunotherapy of cancer (8184), against the estrogen receptor modulator tamoxifen, which is used in therapy of breast cancer (8587), against the antiarrhythmic drug amiodarone (88), against the beta -adrenergic agonists isoproterenol (55) and isoprenaline (8992), against nicotine (9395), against oxidized low-density lipoprotein (LDL) (96), against oxidized fish oil (97), against high glucose levels (96, 98110), against fructose (111122), against galactose (123), against advanced glycation end-products (AGEs) (100, 124, 125), against homocysteine (126–130), against the anti-inflammatory drugs ibuprofen (131) and indomethacin (132, 133), against the herbicide paraquat (65, 134, 135), against carbon tetrachloride (136149), against menadione (150), against 1,4-naphtoquinone (137, 139), against hydrazine (137, 139), against trinitrobenzene sulfonic acid (151, 152), against acrylonitrile (153), against perchloroethylene (154), against methylene dianiline (155), against arsenic (156164), against cadmium (…”
Section: Evidence Showing That Taurine Functions As a Biological Antimentioning
confidence: 99%